2022
DOI: 10.3389/feduc.2022.788418
|View full text |Cite
|
Sign up to set email alerts
|

Distance Lesson Study in Mathematics: A Case Study of an Italian High School

Abstract: The COVID-19 pandemic put teachers and students in virtual classrooms, necessitating the Lesson Study to be adapted to such a new context. In this paper, we investigate how the roles of teachers, observers, and students are changing, considering the use of Information and Communication Technology (ICT) as the only medium of communication. The research methodology is based on the Documental Approach to Didactics, including Instrumental Genesis. It is a qualitative internal case study. The data was collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…LS is just one of the possible teacher education models that can be framed in Cultural Transposition. Probably one of the most emblematic, and others have been shown in previous research (transposition of Chinese problems with variation: Mellone et al, 2019;of the El'konin-Davydov curriculum: Mellone et al, 2020;of the Thinking Classroom: Mellone et al, 2021; of the LS in Distance Education during the COVID pandemic: Ramploud et al, 2021;Capone et al, 2022a, Capone et al, 2022b, or for some other practices the need for Cultural Transposition has been postulated for the exportation of practice (transposition of the Reggio Emilia Approach: Landi & Pintus, 2022).…”
Section: Cultural Transpositionmentioning
confidence: 92%
See 2 more Smart Citations
“…LS is just one of the possible teacher education models that can be framed in Cultural Transposition. Probably one of the most emblematic, and others have been shown in previous research (transposition of Chinese problems with variation: Mellone et al, 2019;of the El'konin-Davydov curriculum: Mellone et al, 2020;of the Thinking Classroom: Mellone et al, 2021; of the LS in Distance Education during the COVID pandemic: Ramploud et al, 2021;Capone et al, 2022a, Capone et al, 2022b, or for some other practices the need for Cultural Transposition has been postulated for the exportation of practice (transposition of the Reggio Emilia Approach: Landi & Pintus, 2022).…”
Section: Cultural Transpositionmentioning
confidence: 92%
“…We could say that Italian researchers are, at the moment, more interested in the general "philosophy" of LS, with special regards to the collaborative setting for planning a lesson in detail (Capone et al, 2020). From these studies, further experiments are being conducted in Piemonte, Lombardia, Valle d'Aosta, and more recently in southern Italy: Naples (Ribeiro et al, 2019) and Salerno (Capone et al, 2022a;this paper). An essential emphasis is provided to the cultural background in which the teaching processes occur (Bartolini Bussi & Martignone, 2013;Mellone et al, 2019).…”
Section: Lesson Study In Italymentioning
confidence: 99%
See 1 more Smart Citation
“…Lesson study as a strategy for teaching As earlier indicated, LS is a strategy for teachers to collaborate in the study of mathematical content, discuss learning objectives, plan lessons together, observe the presented lessons and reflect to improve the teaching and learning (Capone et al, 2022). Buchard and Martin (2017) propose the generic process of LS as recruiting participants, choosing the lesson's topic, planning lessons together, researching the lesson's aspects, and discussing and sharing the outcomes after the debriefing sessions.…”
Section: Related Literaturementioning
confidence: 99%
“…Professional development (PD) has always been considered specialized instruction provided by some educational experts at a specific time and location (Guskey, 2002). Teacher PD is the primary key to improving the quality of education (Capone et al, 2022;Desimone, 2011). The role of teachers is not only to convey student performance information but also to decide the progress of the education transformation (Mohd Shahali et al, 2018).…”
Section: Introductionmentioning
confidence: 99%